DEVELOPMENT OF RELIGIOUS CHARACTERS AND ATTITUDES OF NATIONALISM IN SMP NEGERI 6 KOTA SALATIGA - Akhsin Rafika Dani (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2021)
This study aims to determine the pattern of fostering the religious character and attitude of nationalism of the students of SMP Negeri 6 Salatiga, the supporting and inhibiting factors and the connectivity between the two. This research is a qualitative research with a naturalistic descriptive approach. Data collection techniques using interview methods, observation and documentation. Character building in students uses exemplary, habituation, mau'izah, amtsal, tsawab and i'qab methods. The character building process has both inhibiting and supporting factors. Inhibiting factors in the form of funds used using independent funds, lack of student awareness and discipline, different student backgrounds, student human error, lack of provisions for learning to read and write Al-Quran, lack of controling from teachers, developments in science and technology such as gadgets or cellphones, there are figures that students fear and the covid-19 pandemic. Supporting factors are adequate school facilities, high student interest and direct assistance from teachers and counseling teachers. The results showed that the religious attitudes and attitudes of nationalism had an interrelated relationship with each other, where the religious character of the students was good, the attitude of nationalism was also good.